2021
DOI: 10.1111/cas.14910
|View full text |Cite
|
Sign up to set email alerts
|

The roles and regulation of the KLF5 transcription factor in cancers

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 202 publications
(824 reference statements)
0
53
0
Order By: Relevance
“…These are essential for development, differentiation, and homeostasis 39,40 , suggesting the importance of these TFs in SWF and F1 stages. In contrast, POF-specific peaks in GCs are enriched in motifs corresponding to TFs involved in cytotoxicity and apoptosis induction [41][42][43] , including KLF5, PITX1, and OTX1 (Supplementary Fig. 6d).…”
Section: Resultsmentioning
confidence: 99%
“…These are essential for development, differentiation, and homeostasis 39,40 , suggesting the importance of these TFs in SWF and F1 stages. In contrast, POF-specific peaks in GCs are enriched in motifs corresponding to TFs involved in cytotoxicity and apoptosis induction [41][42][43] , including KLF5, PITX1, and OTX1 (Supplementary Fig. 6d).…”
Section: Resultsmentioning
confidence: 99%
“…TNBC was suggested to be classified into four different subtypes [57]. KLF5 is highly expressed in basal-like breast cancers, including HCC1937 and HCC1806 cell lines, in contrast, KLF5 is lowly expressed in MDA-MB-231 cell line [20]. HDACi also decreased the KLF5 protein expression levels in two different BLBC cell lines, such as BT549 and SUM149PT (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that high expression levels of KLF5 are significantly associated with an increased risk of recurrence and poor prognosis in breast cancer patients [19]. KLF5 is a potential therapeutic target for BLBC [20]. KLF5 depletion suppresses BLBC initiation, growth, and metastasis [17,21].…”
Section: Ivyspringmentioning
confidence: 99%
“…Textmining STRING [71] interacts with GATA4 and GATA6 [90] was the regulator in KATO III gastric cancer cells. It is possible that the difference may arise from the different histopathological phenotypes because KATO III is a human gastric signet ring cell adenoma cancer that can be induced to adipogenic, chondrogenic, osteogenic, and neurogenic differentiation [91].…”
Section: Mfhas1mentioning
confidence: 99%